Brucella abortus-stimulated platelets actívate brain microvascular endothelial cells - Rodríguez, Ana María (2017)
Central nervous system invasion by bacteria of the genus Brucella results in an inflammatory disorder called neurobrucellosis. Bloodbrain barrier activation is a common feature of human neurobrucellosis, but the underlying mechanisms are largely unknown. The aim of this work was to investigate the influence of B. abortus (B.a.)-activated platelets (PTL) on human brain microvascular endothelial cells (HBMEC). For this, supernatants (SN) from B.a.-stimulated human PTL were used to stimulate HBMEC. Expression of ICAM-1 (CD54) and secretion of IL-6, IL-8 and MCP-1 were evaluated to determine HBMEC´ activation. SN from B.a.-stimulated PLT induced a significant secretion of IL-6, IL-8, MCP-1 and the up-regulation of CD54 expression in a dose-dependent manner compared with SN from unstimulated PLT (p<0.001).To avoid the possible implication of B.a. outer membrane vesicles (OMV) we ultra-centrifuged the SN (to eliminate OMV). HBMEC were stimulated with ultra-centrifuge SN and we observed no differences on HBMEC’ activation compared with non-centrifuge SN (p>0.05), demonstrating that a soluble factor released from PLT was implicated on HBMEC’ activation. SN from heat-killed B.a.-stimulated PTL also activated HBMEC indicating that B.a.’ viability was not necessary in activating PLT. Soluble CD40L was not implicated on HBMEC’ activation, as an anti-CD40L antibody could not block cytokine secretion or ICAM-1 up-regulation. Treatment of SN with trypsin eliminate the effect (p<0.0005), demonstrating that the PLT effector is a protein. These results demonstrate that B.a.-stimulated PTL can activate brain endothelial cells, and this could be implicated on the entry to B.a. to the central nervous system